The Presence of God in the Community: The Eucharist in its Early Christian Cultic Context - Aune, David Edward (Scottish journal of theology, 1976)
Every religion has an overall structure which both gives meaning to and derives it from each of its constituent parts. Ordinarily, this structure may be seen in its most essential form in cultic worship where religious experience both is determined by and itself determines the shape and meaning of religious traditions. In contemporary Roman Catholicism, for example, the Eucharist is understood in several ways due to the variety of possible contexts in which the Mass may be experienced; a religious community and a parish church are examples of widely diverging contexts. However, if we wish to understand the significance and place of the Eucharist in a period as remote and as different from our own as that of first century Christianity, we are faced with a radically different problem. One popular approach to such an inquiry would carefully examine the theme of the Lord's Supper throughout the New Testament and other early Christian literature so that the results of the study could be used to compare and contrast the Eucharist (s) of early Christianity with that of one or another modern Christian denomination. The all but unavoidable result of this approach would be the tendency of each theological tradition to retroject its own understanding of the Eucharist back into the early Church, whether it would find itself at home there or not.